PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN PARIWISATA DI TAMAN NASIONAL KARIMUNJAWA - Madyaningrum, Ika Ristiyani; Utomo, Aloisius Chris Cahyo; Pratama, Yudha Wahyu (KRITIS, 2019)
This article specifically discusses the participation of local communities in tourism development in Karimunjawa National Park, which is administratively a part of Jepara Regency, Central Java Province. This research uses a qualitative approach, the research findings show that the participation of local communities in Karimunjawa is realized through the formation of the Tourism Local Transportation Association, the Lodging Association, the Tourism Ship Association, the Culinary Association, and the Tour Guides Association which are members of the Indonesian Tour Guides Association. also encouraged to offer local Karimunjawa superior products in the form of food, beverages, and handicraft products to tourists visiting Karimunjawa to support the economic development and empowerment of the Karimunjawa community.